2012
DOI: 10.2174/157489112801619665
|View full text |Cite
|
Sign up to set email alerts
|

Recent Patents Regarding Essential Oils and the Significance of their Constituents in Human Health and Treatment

Abstract: Essential oils derived from aromatic plants possess useful properties concerning human health, such as antibacterial, antiviral and antifungal activities. They can be used as natural alternatives to synthetic preparations to prevent and treat infectious diseases caused by multidrug resistant microorganisms. They are used successfully to treat respiratory tract, digestive system and skin infections. Many of them may be applied in anticancer therapy, cardiovascular and nervous system disorders, as well as to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 0 publications
1
18
0
3
Order By: Relevance
“…In recent years, studies on the biological activities of extracts from plants have become increasingly important in the search for natural and safe alternative medicines [10], with increased interest particularly in essential oils derived from aromatic medicinal plants [11, 12]. Essential oils are odorous, volatile products of plant secondary metabolism and they are found in leaves, stems, seeds, flowers, or other parts of aromatic plants [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies on the biological activities of extracts from plants have become increasingly important in the search for natural and safe alternative medicines [10], with increased interest particularly in essential oils derived from aromatic medicinal plants [11, 12]. Essential oils are odorous, volatile products of plant secondary metabolism and they are found in leaves, stems, seeds, flowers, or other parts of aromatic plants [11].…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils have gained interest as potential sources for bioactive natural molecules and are the subject of studies for their possible use as alternative medications for the treatment of infectious diseases. The long known antimicrobial actions of essential oils are now being extensively scientifically reviewed and applied in health and industry fields . Various in vitro studies have confirmed the inhibitory action of essential oils against bacteria, fungi, yeasts, viruses and protozoa .…”
Section: Introductionmentioning
confidence: 99%
“…Al menos 3000 se han identificado y 300 están comercialmente disponibles para diversos usos como la fabricación de perfumes, cosméticos, productos de limpieza, insecticidas, conservantes y aditivos de alimentos (1)(2)(3)(4)(5). Los AE también están presentes en formulaciones de medicamentos homeopáticos, por ejemplo, la aplicación tópica se usa para tratar el acné, dermatomicosis y otras afectaciones de la piel, la aromaterapia para infecciones del tracto respiratorio y afecciones del sistema nervioso y el efecto anticancerígeno están bien documentado (6)(7)(8)(9). Varios estudios sugieren que estas propiedades medicinales se deben en gran parte a fortalecimiento del sistema inmune (7,10).…”
Section: Introductionunclassified
“…Los AE también están presentes en formulaciones de medicamentos homeopáticos, por ejemplo, la aplicación tópica se usa para tratar el acné, dermatomicosis y otras afectaciones de la piel, la aromaterapia para infecciones del tracto respiratorio y afecciones del sistema nervioso y el efecto anticancerígeno están bien documentado (6)(7)(8)(9). Varios estudios sugieren que estas propiedades medicinales se deben en gran parte a fortalecimiento del sistema inmune (7,10).…”
Section: Introductionunclassified
See 1 more Smart Citation